A Comparative Study of Conventional Physiotherapy versus Robot-Assisted Gait Training Associated to Physiotherapy in Individuals with Ataxia after Stroke - Marcia Belas dos Santos; Clarissa Barros de Oliveira; Arly dos Santos; Cristhiane Garabello Pires; Viviana Dylewski; Ricardo Mario Arida (Behavioural Neurology)
Objectives. To assess the influence of RAGT on balance, coordination, and functional independence in activities of daily living of chronic stroke survivors with ataxia at least one year of injury. Methods. It was a randomized controlled trial. The patients were allocated to either therapist-assisted gait training (TAGT) or robotic-assisted gait training (RAGT). Both groups received 3 weekly sessions of physiotherapy with an estimated duration of 60 minutes each and prescribed home exercises. The following outcome measures were evaluated prior to and after the completion of the 5-month protocol treatment: BBS, TUG test, FIM, and SARA. For intragroup comparisons, the Wilcoxon test was used, and the Mann–Whitney test was used for between-group comparison. Results. Nineteen stroke survivors with ataxia sequel after one year of injury were recruited. Both groups showed statistically significant improvement (P<0.05) in balance, functional independencein, and general ataxia symptoms. There were no statistically significant differences (P<0.05) for between-group comparisons both at baseline and after completion of the protocol. Conclusions. Chronic stroke patients with ataxia had significant improvements in balance and independence in activities of daily living after RAGT along with conventional therapy and home exercises. This trial was registered with trial registration number 39862414.6.0000.5505.